The vegetable garden pest handbook : identify and solve common pest problems on edible plants - Mulvihill, Susan (Cool Springs Press, 2021)
Pests in your garden are a challenge no one wants to face but very few gardeners manage to escape. Instead of turning to synthetic chemical sprays, baits, and dusts, Mulvihill shows you how to handle even your worst pest woes naturally. You'll learn to identify common vegetable garden pests, based on both the damage they cause and their physical appearance. Then you'll discover the most effective organic pest-control products to minimize damage while still preserving pollinators and other beneficial insects. -- adapted from back cover